Analisis Perlakuan Akuntansi Aset Biologis Agrikultur Pada Usaha Perkebunan Green Venus Garden - Ni Putu Dita Pradnyani; Sang Ayu Putu Arie Indraswarawati (UNHI Press, 2023)
This stuidy aims to determine the accouinting treatment of biological assets in the Green Venuis Garden plantation buisiness. This stuidy uised a quialitative analysis method with data obtained throuigh observation, interviews and also docuimentation of informants related to the Green Venuis Garden plantation. The analysis techniquie uised is descriptive comparative analysis, in which the researcher describes the findings derived from the data collected throuigh the observation process on the research object which will then be compared with the biological asset accouinting treatment method based on PSAK No. 69 on agricuiltuire in theory which has been developing in academic circles. Based on the resuilts of the research and discuission, it can be concluided that the accouinting treatment of the biological assets of the Green Venuis Garden Plantation is not in accordance with PSAK 69 becauise there is still muich that needs to be adjuisted again.